Detection of specific Atlantic salmon antibodies against salmonid alphavirus using a bead-based immunoassay. Issue 106 (November 2020) - Teige, Lena Hammerlund; Aksnes, Ida; Røsæg, Magnus Vikan; Jensen, Ingvill; Jørgensen, Jorunn; Sindre, Hilde; Collins, Catherine; Collet, Bertrand; Rimstad, Espen; Dahle, Maria K.; Boysen, Preben
Abstract: Salmonid alphavirus (SAV) is the etiological cause of pancreas disease (PD) in Atlantic salmon ( Salmo salar ). Several vaccines against SAV are in use, but PD still cause significant mortality and concern in European aquaculture, raising the need for optimal tools to monitor SAV immunity. To monitor and control the distribution of PD in Norway, all salmonid farms are regularly screened for SAV by RT-qPCR. While the direct detection of SAV is helpful in the early stages of infection, serological methods could bring additional information on acquired SAV immunity in the later stages. Traditionally, SAV antibodies are monitored in neutralization assays, but they are time-consuming and cumbersome, thus alternative assays are warranted. Enzyme-linked immunosorbent assays (ELISAs) have not yet been successfully used for anti-SAV antibody detection in aquaculture. We aimed to develop a bead-based immunoassay for SAV-specific antibodies. By using detergent-treated SAV particles as antigens, we detected SAV-specific antibodies in plasma collected from both a SAV challenge trial and a field outbreak of PD. Increased levels of SAV-specific antibodies were seen after most fish had become negative for viral RNA. The bead-based assay is time saving compared to virus neutralization assays, and suitable for non-lethal testing due to low sample size requirements. We conclude that the bead-based immunoassay for SAV antibody detection is a promising diagnostic tool to complement SAV screening in aquaculture. Graphical abstract: Image 1 Highlights: A bead-based serological assay for Salmonid alphavirus (SAV) was developed. Detergent-treated whole SAV particles were useful to detect specific SAV antibodies in Atlantic salmon. Low background binding was shown in experimental as well as field samples. Seropositivity was demonstrated after SAV (detected by RT-qPCR) is cleared from the host. The assay correlated well with a virus neutralization test in a set of field samples.